2008
DOI: 10.1128/aac.01603-07
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Genomic Screen in Saccharomyces cerevisiae Reveals a Role for Diphthamidation of Translation Elongation Factor 2 in Inhibition of Protein Synthesis by Sordarin

Abstract: Sordarin and its derivatives are antifungal compounds of potential clinical interest. Despite the highly conserved nature of the fungal and mammalian protein synthesis machineries, sordarin is a selective inhibitor of protein synthesis in fungal organisms. In cells sensitive to sordarin, its mode of action is through preventing the release of translation elongation factor 2 (eEF2) during the translocation step, thus blocking protein synthesis. To further investigate the cellular components required for the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 50 publications
6
45
0
2
Order By: Relevance
“…In an effort to further study diphthamide function and the interrelation between components of the diphthamide pathway, we found by co-immune precipitation and tandem affinity purification protocols that the Dph1, Dph2 and Dph3 factors form a protein complex, assembly of which is crucial for EF2 ADP-riboslyation by DT (Fichtner et al, 2003;Bär et al, 2008). Moreover, we and others discovered that the Dph1-Dph5 proteins are all required for the cytotoxic activity of sordarin Botet et al, 2008), another EF2-related antifungal and translation inhibitor (Justice et al, 1998). When using biotin-labeled NAD + as donor for the in vitro ADP ribosylation assay, wild-type strains display EF2 ADP-ribosylation acceptor activity (indicated by the arrow) whereas diphthamide mutans dph1 and dph5 fail to do so.…”
Section: Posttranslational Biosynthesis Of Diphthamide On Ef2mentioning
confidence: 99%
See 3 more Smart Citations
“…In an effort to further study diphthamide function and the interrelation between components of the diphthamide pathway, we found by co-immune precipitation and tandem affinity purification protocols that the Dph1, Dph2 and Dph3 factors form a protein complex, assembly of which is crucial for EF2 ADP-riboslyation by DT (Fichtner et al, 2003;Bär et al, 2008). Moreover, we and others discovered that the Dph1-Dph5 proteins are all required for the cytotoxic activity of sordarin Botet et al, 2008), another EF2-related antifungal and translation inhibitor (Justice et al, 1998). When using biotin-labeled NAD + as donor for the in vitro ADP ribosylation assay, wild-type strains display EF2 ADP-ribosylation acceptor activity (indicated by the arrow) whereas diphthamide mutans dph1 and dph5 fail to do so.…”
Section: Posttranslational Biosynthesis Of Diphthamide On Ef2mentioning
confidence: 99%
“…In addition, possible effector roles of YBR246w and YLR143w for EF2 specific antifungals including sordarin are becoming evident: when deleted, these new loci not only affect the communication between Dph5 and EF2 but also phenocopy traits (including sordarin resistance) that are typical of dph1, dph2, dph3, dph4 and dph5 mutants from yeast Botet et al, 2008;Carette et al, 2009). Although being aware that the sordarin phenotype may also be ascribable to defects in EF2-unrelated genes that are required for binding and/or import of the deadly antifungal (Botet et al, 2008), we consider these ORFs to be candidate diphthamide biosynthesis genes. In support of this notion, preliminary data based on in vitro EF2 modification assays demonstrate that inactivation of YBR246w and YLR143w eliminates the ADP-ribosylation acceptor activity of EF2 in the presence of DT.…”
Section: Posttranslational Biosynthesis Of Diphthamide On Ef2mentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 In contrast, the eEF2 defect might affect the sensitivity toward another translation inhibitor, namely sordarin. 44 We showed that the uL11 protein is involved in the reading frame maintenance and translation fidelity. The lack of the uL11 protein on the ribosome induces both C1 and -1 PRF.…”
Section: Ul11 Involvement In Ribosomal Speed and Accuracymentioning
confidence: 99%